2015
DOI: 10.2174/1567201812666150326113331
|View full text |Cite
|
Sign up to set email alerts
|

Physically Cross-linked Hydrogels of β -cyclodextrin Polymer and Poly(ethylene glycol)-cholesterol as Delivery Systems for Macromolecules and Small Drug Molecules

Abstract: An injectable hydrogel based on the inclusion complexation of polymerized β-cyclodextrin (pβ-CD) and cholesterol terminated poly(ethylene glycol) (PEG-chol) was developed and used as a delivery system for both macromolecules and small drugs. The hydrogel was characterized by different analyses including X-ray diffraction, differential scanning calorimetry and scanning electron microscopy. The effects of pβ-CD/PEG-chol ratio and PEG-chol architecture on the hydrogel properties were also investigated. Cytotoxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…In contrast, formula B did not show any cross-over point because the values of G > G for the whole rheogram, which indicates the viscous behaviors of the system. This finding and interpretation were in agreement with previously reported data, where PEG-chol exhibits a higher affinity to β-CD when compared with PEG-Ad [34].…”
Section: Rheological Propertiessupporting
confidence: 94%
“…In contrast, formula B did not show any cross-over point because the values of G > G for the whole rheogram, which indicates the viscous behaviors of the system. This finding and interpretation were in agreement with previously reported data, where PEG-chol exhibits a higher affinity to β-CD when compared with PEG-Ad [34].…”
Section: Rheological Propertiessupporting
confidence: 94%
“…The hydrophobic host cavity of CD has been well described in hydrogel systems, where it can be used to interact with other hydrophobic molecules, or guests, in supramolecular complexes [42,47]. Of these guests, cholesterol has been one of the most commonly described, where its ability to complex CD has been used for a variety of biomaterial applications [4850]. Thus, we hypothesized that CD inclusion would sequester cholesterol-modified siRNAs and attenuate their passive release from hydrogels, paralleling previous reports of the use of CD to retain and sustain small molecule release [42,47].…”
Section: Resultsmentioning
confidence: 99%
“…Multimolecular inclusion complex formation has been the main objective of our study which has been successfully accomplished as suggested by the entrapment ratio of gefitinib and simvastatin as 3 ± 0.48 : 2 ± 0.19. Earlier reports are there to formulate individual molecules of the aforementioned drugs as monomolecular inclusion complex; however, this is the first approach to manufacture single inclusion complex containing more than one drug molecule which would be cost effective and rapid in its action than conventional method of cross‐linking of BCD monomers. The characterization of the inclusion complex by different methods such as FT‐IR, DSC, XRD and DLS further confirmed that there is a formation of inclusion complex of both the drugs with BCD.…”
Section: Resultsmentioning
confidence: 99%
“…In pursuit, we are currently working on this process to upregulate both gefitinib and simvastatin release significantly through our microparticles. Although previous authors acknowledged that cross‐linked β‐cyclodextrins, hydrogels or nanosponges could offer value added release to drugs and that seems to be an alternate route to increase such solubilities; these methods often fall costlier due to the expensive cross‐linking polymers involved herewith. Moreover, such processes are tedious due to cross‐linking reaction with the polymeric agents, maintaining its specificity and eliminating its toxic by‐products.…”
Section: Discussionmentioning
confidence: 99%